Efforts of Catholic Religious Education Teachers in Overcoming Verbal Violence in Students at 1 Delitua State Senior High School - Benediktus Benteng Kurniadi; Gina Patrecia Simarmata; Ermina Waruwu (International Journal of Scientific Multidisciplinary Research, 2023)
This study aims to answer research problems about efforts of catholic religious education teachers in overcoming verbal violence in students at 1 Delitua State Senior High School.This study uses a descriptive qualitative approach. This research is conducted at 1 Delitua State Senior High School from February to April 2023. The research subjects are selected by purposive sampling. The informants determined by the researcher are 15 people consisting of catholic religion teachers, school principals, student affairs teachers, guidance and counseling teachers, peer teachers, and 10 students. Data analysis is carried out by means of data reduction, data presentation, and research conclusions. The results of the study show that verbal violence occurs in the school environment in the form of yelling, cursing, humiliating, intimidating, belittling and humiliating, and verbal bullying. Efforts made by the teacher in overcoming verbal violence in the communication aspect, namely the teacher approaches students and provides direction so that students dare to convey the forms of violence they experience